2014
DOI: 10.1186/2193-1801-3-381
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation of FANCA and BRCA1 in human cells

Abstract: Fanconi anemia (FA) is a genetically heterogeneous syndrome associated with increased cancer predisposition. The underlying genes govern the FA pathway which functions to protect the genome during the S-phase of the cell cycle. While upregulation of FA genes has been linked to chemotherapy resistance, little is known about their regulation in response to proliferative stimuli. The purpose of this study was to examine how FA genes are regulated, especially in relation to the cell cycle, in order to reveal their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, hypomethylation of FANCA promoters in squamous cell carcinoma of larynx (LSCC) cells has also been shown [ 160 ], which could mean that higher expression levels of these proteins contribute to oncogenic potential. Consistent with this, FANCA expression is up-regulated in basal breast tumors compared with non-basal breast tumors, and has higher expression levels in RB1 -mutated retinoblastomas than MYCN -amplified retinoblastomas [ 161 ].…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, hypomethylation of FANCA promoters in squamous cell carcinoma of larynx (LSCC) cells has also been shown [ 160 ], which could mean that higher expression levels of these proteins contribute to oncogenic potential. Consistent with this, FANCA expression is up-regulated in basal breast tumors compared with non-basal breast tumors, and has higher expression levels in RB1 -mutated retinoblastomas than MYCN -amplified retinoblastomas [ 161 ].…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, a coregulation of BRCA1 and BRCA2 has been previously described. 45 BRCA1 is not a predicted target, which supports this assumption.…”
Section: Radiosensitizing Effectsmentioning
confidence: 62%
“…BRCA genes are well-known tumour suppressor genes and mutations in this family of genes can result in high susceptibility to breast cancer and ovarian cancer. BRCA1 negatively regulates the cell cycle [20], and it is known that BRCA and FANCA function together [21]. Previous studies showed that FANCJ and BACH1 (BRCA1-associated C-terminal helicase) [22], FANCD1 and BRCA2, FANCN and PALB2, FANCJ and BRIP1 are the same proteins [23], demonstrating that FA genes and the BRCA gene family are strongly related.…”
Section: Discussionmentioning
confidence: 99%